Cobalt-doped hematite thin films for electrocatalytic water oxidation in highly acidic media. Issue 34 (10th April 2019) - Kwong, Wai Ling; Lee, Cheng Choo; Shchukarev, Andrey; Messinger, Johannes
Abstract : Low-concentration cobalt doping improves the intrinsic activity and charge transport of hematite thin-film electrocatalyst for high-performance acidic water oxidation. Abstract : Earth-abundant cobalt-doped hematite thin-film electrocatalysts were explored for acidic water oxidation. The strategically doped hematite produced a stable geometric current density of 10 mA cm −2 for up to 50 h at pH 0.3, as a result of Co-enhanced intrinsic catalytic activity and charge transport properties across the film matrix.